New private law theory a pluralist approach - Grundmann, Stefan 1958-; Micklitz, Hans-Wolfgang 1949-; Renner, Moritz 1981- (Cambridge University Press, 2021)
New Private Law Theory opens a new pathway to private law theory through a pluralistic approach. Such a theory needs a broad and stable foundation, which the authors have built here through a canon of nearly seventy texts of reference. This book brings these different texts from different disciplines into conversation with each other, grouping them around central questions of private law and at the same time integrating them with the legal doctrinal analysis of example cases. This book will be accessible to both experienced and early career scholars working on private law